Physico-Chemical Study of Tetrabutylammonium Bromide Solutions in Methanol and Ethanol at Different Temperatures - Abbas, Hawazin A; Al-Dujaili, Amar H; Abdul-Ghani, Mohammad J (Al-Nahrain Journal of Science, 2012)
Viscosity and density measurements at concentration range (0.0040-0.1661mole/L) for thetetrabutylammonium bromide (TBABr) solutions in methanol and ethanol at various temperatures(298.15, 303.15 and 308.15 K) are reported. The viscosity A and B coefficient was calculated fromthe Jones–Dole equation and found to be decreased from methanol to ethanol. The Gibbs freeenergy of viscons flow of (TBABr) solutions in methanol and ethanol we’re calculated fromexperimental viscosity measurements using Eyring equation. The apparent molal volumes   forthese solutions at different temperatures we’re also obtained from experimental densitymeasurements.